2010
DOI: 10.1111/j.1365-2036.2010.04270.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation, epidemiological factors and quality of life impairment associated with dyspepsia in urban Malaysia

Abstract: SUMMARY BackgroundThe role of ethnicity in the development of dyspepsia remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 44 publications
(66 reference statements)
1
82
1
Order By: Relevance
“…The prevalence of dyspepsia in the community varies between 5% and 40%, depending on the geographical region under study, but also on the criteria used to define its presence. [1][2][3][4] The condition has significant implications both for sufferers, due to impaired quality of life and sickness absence from work, [5][6][7][8][9] and society as a whole, due to medical expenses arising from managing the condition. A recent questionnaire survey reported that the mean yearly cost of dyspepsia to patients was almost $700, 10 and burden of illness studies in the USA estimated that there were almost 2 million physician visits in 2009 as a result of dyspepsia, 11 and >30% of endoscopies were performed with dyspepsia as the main indication.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dyspepsia in the community varies between 5% and 40%, depending on the geographical region under study, but also on the criteria used to define its presence. [1][2][3][4] The condition has significant implications both for sufferers, due to impaired quality of life and sickness absence from work, [5][6][7][8][9] and society as a whole, due to medical expenses arising from managing the condition. A recent questionnaire survey reported that the mean yearly cost of dyspepsia to patients was almost $700, 10 and burden of illness studies in the USA estimated that there were almost 2 million physician visits in 2009 as a result of dyspepsia, 11 and >30% of endoscopies were performed with dyspepsia as the main indication.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences in H. pylori prevalence between high and low-income countries because H. pylori infection is strongly related to economic conditions (17). H. pylori incidence also increases with age largely due to the birth cohort effects.…”
Section: The Common Risk Factors For H Pylori Infection Ismentioning
confidence: 99%
“…The most common accepted routes of transmission are fecal-oral in developing countries, and gastro-oral route in developed countries. There are many risk factors for H. pylori infection including: overpopulation/congested houses, family sizes, unsafe sources of water, and low socioeconomic status (17).…”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%
“…4,5 Similarly, Rome III should benefit from further empirical validation aided by explicitly defined inclusion of sub-threshold conditions to ascertain its internal and external validities -namely socioeconomic associations. In this sense, adopting for Rome III the approach previously taken by Mahadeva et al in examining the ethnic and HRQOL associations 6,7 would be salient in further research on epidemiology of dyspepsia.…”
mentioning
confidence: 99%